An animated textbook of creative stories of pitta nympha integrated with filial piety and gratitude - Weng, Tingsheng (Technium Social Sciences Journal, 2022)
Meaningful animated stories can bring readers the correct values, enhance their knowledge, and have the correct guiding role of social moral feelings. Pitta nympha, a rare and attractive protected bird, was used as the theme in this study, and animation software was used to draw the characters and plot effects. This study created a textbook for animation technology courses and provided it to schools as a textbook for homeland and natural education, which has been recognized by teachers and students. The results show that animated education can strengthen students’ cognition of animal conservation and guide students to think about the importance of animal conservation, thus, inducing their behaviors of animal conservation. Moreover, animations can enrich students’ knowledge structure and stimulate emotions, including filial piety and gratitude. Guiding the development of the true, the good, and the beautiful, the contents of this multi-culture media presentation can also be printed as paper-based picture textbooks for educational purposes